PERFORMATIVE UTTERANCES ON EFL CLASSROOM IN SMP ISLAM CENDEKIA HARAPAN JOMBANG - Muhammad Saibani Wiyanto; Suparti Suparti; Siti Romlah (STKIP PGRI Jombang, 2023)
This article aimed to examine performative utterances in the interactions between teacher and students in EFL classroom. It adopted a sociolinguistic and content analysis approach, focusing on the field of performative utterances as the subject of study. The research employed a descriptive qualitative method. The primary data source was an audio recording capturing the interactions between teacher and students at SMP Islam Cendekia Harapan Jombang. The researcher used J.L. Austin's theoryÂ in the Wardhaugh book (2010:286) for data analysis. Based on the theory there are five types of performative utterance: verdictives, exercitive, commisives, behabitives, and expositives. The findings are the teacher's utterances consisted of 21 utterances, with 33% (7 utterances) categorized as exercitives, 24% (5 utterances) as expositives, 19% (4 utterances) as verdictives, 14% (3 utterances) as commissives, and 10% (2 utterances) as behabitives. On the other hand, the students' utterances amounted to 14 utterances, with 46% (5 utterances) classified as expositives, 27% (3 utterances) as verdictives, 18% (2 utterances) as behabitives, and 9% (1 utterance) as exercitives. There were no utterances of commissive use in students utterances.